Penyelesaian Wanprestasi dalam Pembiayaan Pemilikan Rumah (KPR Syariah) dengan Akad Murabahah - Maryani Maryani (Universitas Islam Raden Rahmat, 2022)
Sharia financing products have developed in the banking world, in addition to more banking institutions that offer products in Islam such as murabahah contracts. Murabahah contract is a contract of sale and purchase of goods between two parties whose price and profit are mutually agreed upon. In the process of Sharia Mortgage (KPR Syariah) at BTN (Bank Tabungan Negara) Syariah Probolinggo, many use murabahah contracts and various problems or problems that arise and need to be resolved. One of the problems that often arise in the implementation of home ownership loans is the default. The purpose of this study is to explain the form of default in the implementation of home ownership loans, the factors that cause default, and the settlement of defaults in the implementation of home ownership loans at BTN Syariah Probolinggo. The results of the study indicate that the form of default in the implementation of Sharia mortgages at BTN Syariah Probolinggo Branch is that the debtor is late in carrying out its obligations as previously agreed.